Innate Lymphoid Cells in Renal Inflammation - Becker, Martina; Gnirck, Ann-Christin; Turner, Jan-Eric (Frontiers in Immunology, 2020)
Since their identification as a separate family of leukocytes, Innate Lymphoid Cells (ILCs) have been shown to play crucial roles in immune-mediated diseases and repair mechanisms that restore tissue integrity after injury. ILCs mainly populate non-lymphoid tissues where they form intricate circuits with parenchymal cells to regulate tissue immunity and organ homeostasis. However, the specific phenotype and function of ILC populations that reside in specific anatomical locations, such as the kidney, still remains poorly understood. In this review, we discuss tissue-specific properties of kidney-residing ILCs and summarise recent advances in the understanding of ILC biology in kidney diseases that might pave the way for development of novel treatment strategies in humans.